О проявлении этнического синкретизма в среде лесостепного салтовского населения (на примере материалов раскопа–4 селища Коробовы Хутора) - Колода, В.В. (My University, 2008)
V. Koloda. About evincing ethnic syncretism among forest-steppe Saltov population (by the example of excavation-4 materials at Korobovy Khutora settlement) The work is devoted to analysis of the Early Middle Ages materials (Saltov ar-chaeological culture of the middle of VIII—the middle of X centuries) from Korobovy Khutora settlement in Kharkiv region. The materials that have been found in the excavation № 4 tell us about polyethnic population of this settlement. Different ethnic groups lived there (such as Turkic-Bulgarian, ancient Hungarian and Slavonic ones) while the Alans — native of Northern Caucasia — were dominating. It is proved by ceramic material, traditions of house building, elements of interior and the heating device found there.